A new fossil jewel beetle (Coleoptera: Buprestidae) from the Early Cretaceous of Inner Mongolia, China - Yu, Yali; Ślipiński, Adam; Shih, Chungkun; Pang, Hong; Ren, Dong (Zootaxa, 2013)
A new fossil buprestid, Trapezitergum grande Yu, Ślipiński et Shih, gen. et sp. nov., from the Early Cretaceous Yixian Formation of Liutiaogou Village, Tianyi County, Inner Mongolia, China, is described and placed in the subfamily Buprestinae.